2017
DOI: 10.1007/s10620-017-4818-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angiogenesis in Chronic Radiation Proctitis: New Evidence Favoring Inhibition of Angiogenesis Ex Vivo

Abstract: Angiostatin increased and had a distinct distribution in CRP lesions. Compensatory telangiectasia in the mucosa, vessel stenosis, and reduced MVD might attenuate blood flow in the submucosa and contribute to CRP progression. Restoration of vascular functionality by promoting angiogenesis in the submucosal layer may help alleviate CRP in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…A recent study, on the other hand, suggested a strong role of submucosal microvascular changes leading to onset and progression of CRP[34]. Researchers collected fresh surgical rectal specimens from 30 patients with CRP and 29 patients without CRP that allowed assessment of the entire rectal wall for immunohistochemistry arrays of angiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study, on the other hand, suggested a strong role of submucosal microvascular changes leading to onset and progression of CRP[34]. Researchers collected fresh surgical rectal specimens from 30 patients with CRP and 29 patients without CRP that allowed assessment of the entire rectal wall for immunohistochemistry arrays of angiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that angiostatin deposits that reside within rectal vessels are perfused throughout the mucosal-submucosal layer upon radiation damage of the endothelial cells. Angiostatins subsequently suppress microvessel formation, causing vessel stenosis and fibrotic vascular sclerosis, decreasing microvessel density in the submucosal layer[34]. The vascular changes and formation of telangiectasias in the mucosal layer are hypothesized to be compensatory changes in response to the alteration of microvasculature in the submucosal layer.…”
Section: Discussionmentioning
confidence: 99%
“…The RIS system is a popular method for evaluating radiation injury in general [ 14–17 ]. We also used in parallel the expression level and distribution pattern of angiostatin as two parameters to evaluate the severity of radiation-induced damage [ 8 ]. Interestingly, we found that the changes in angiostatin were consistent with the changes in RIS.…”
Section: Discussionmentioning
confidence: 99%
“…Sections with a thickness of 4 µm were sliced from formalin-fixed paraffin-embedded samples and placed on slides for hematoxylin and eosin (HE) and Masson's trichrome stains according to standard protocols. Histopathological assessment of each section was performed by calculating the RIS based on our previous study [ 8 ]. Since all patients enrolled in this study had undergone surgery at approximately 6–8 weeks after irradiation, the pathological changes corresponded to the acute or subacute phase and the basic parameters of the RIS included the following: mucosal ulcerations, mucosal telangiectasia, inflammation, epithelial atypia, submucosal fibrosis, edema, and vascular sclerosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation